2002
DOI: 10.1038/sj.bjp.0704465
|View full text |Cite
|
Sign up to set email alerts
|

Capacitative Ca2+ entry in vascular endothelial cells is mediated via pathways sensitive to 2 aminoethoxydiphenyl borate and xestospongin C

Abstract: 1 Agonists increase endothelial cell intracellular Ca 2+ , in part, by capacitative entry, which is triggered by the ®lling state of intracellular Ca 2+ stores. It has been suggested that depletion of endoplasmic reticulum (ER) Ca 2+ stores either leads to a physical coupling between the ER and a plasma membrane channel, or results in production of an intracellular messenger which a ects the gating of membrane channels. As an axis involving the IP 3 receptor has been implicated in a physical coupling mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 52 publications
8
43
0
Order By: Relevance
“…They traditionally elicit a biphasic [Ca 2+ ]i wave. In agreement with previous reports though in different cell lines such as vascular endothelial cells (Holda and Blatter, 1997;Bishara et al, 2002), gliom C6 (Sabala et al, 1997); (Grimaldi et al, 2003) and astrocytes (Grimaldi et al, 2003), the ATP-triggered Peak 1 was more powerful, sharper, and returned to basal levels faster than that evoked by thapsigargin, which would imply a more exhaustive intracellular calcium store depletion by the former agonist and hence an equally robust Peak 2 (the plateau phase which signify SOCE). Contrary to expectations, thapsigargin caused a more vigorous SOCE.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…They traditionally elicit a biphasic [Ca 2+ ]i wave. In agreement with previous reports though in different cell lines such as vascular endothelial cells (Holda and Blatter, 1997;Bishara et al, 2002), gliom C6 (Sabala et al, 1997); (Grimaldi et al, 2003) and astrocytes (Grimaldi et al, 2003), the ATP-triggered Peak 1 was more powerful, sharper, and returned to basal levels faster than that evoked by thapsigargin, which would imply a more exhaustive intracellular calcium store depletion by the former agonist and hence an equally robust Peak 2 (the plateau phase which signify SOCE). Contrary to expectations, thapsigargin caused a more vigorous SOCE.…”
Section: Discussionsupporting
confidence: 79%
“…To minimize fluorophore photobleaching and cellular phototoxic effects, both laser output and laser power were set at a maximum of 25% and 1%, stimulating the classical phospholipase C enzyme pathway whose downstream inositol triphosphate (IP3) product stimulates the IP3 receptors (IP3R) to release calcium from the intracellular stores. In both scenarios, this constitutes the first cytosolic calcium peak (Peak 1) that is followed by a second peak (Peak 2) constituting the store-operated calcium entry (SOCE) of free calcium ion from the extracellular milieu (Holda et al, 1998;Putney, 2001;Bishara et al, 2002;Targos et al, 2005).…”
Section: [Ca 2+ ] I Imagingmentioning
confidence: 99%
“…Furthermore, Steinert et al (2002) and Mahdy et al (1998) demonstrated that human fetal venous EC and maternal human hand vein EC show a loss of the sustained phase in subjects with preeclampsia, a condition that is characterized by hypertension (Mahdy et al 1998, Steinert et al 2002. This data along with our previous data on UAEC led us to believe that the sustained phase of the [Ca 2C ] i response in NP-UAEC is relatively unresponsive, while P-UAEC mobilize Ca 2C more like calf pulmonary artery EC, bovine aortic EC, and rat aortic EC (Chu et al 2000, Bishara et al 2002, Wilkinson & Jacob 2003.…”
Section: Introductionmentioning
confidence: 71%
“…It has been shown that Ca 2ϩ ionophores promote intracellular Ca 2ϩ store depletion and subsequent SOCE (43)(44)(45). In this context, we can reasonably assume that the effects of the different compounds used here on A23187-induced Ca 2ϩ response are relevant to Ca 2ϩ entry mediated by store depletion or to Ca 2ϩ release from intracellular stores.…”
Section: Discussionmentioning
confidence: 99%